Not Always Black and White: Colour Aberrations in the Dovekie - Jakubas, Dariusz; Wojczulanis-Jakubas, Katarzyna (ARCTIC, 2012)
We describe four records of colour aberrations in the dovekie (Alle alle). During six years of studies of breeding ecology in two large dovekie colonies in West Spitsbergen, we recorded one albino chick (white feathers, red eyes, pinkish legs and feet), one adult or subadult with a “brown” aberration (all black parts turned dark brown), one adult in a typical summer plumage with depigmented (pinkish) legs and feet, and one chick in a typical plumage, but with whitish feathers on back and wing coverts. Albinism and “brown” mutations are heritable traits. The two remaining colour aberrations probably have been acquired and might have been caused by disease, malnutrition, or other unknown factors. Nous décrivons quatre mentions d’aberrations de couleur chez le mergule nain (Alle alle). Au cours de six années d’étude en écologie des oiseaux nicheurs au sein de deux grandes colonies de mergules nains de Spitzberg Ouest, nous avons dénoté un oisillon albinos (ailes blanches, yeux rouges, pattes et pieds rosés), un adulte ou jeune adulte doté d’une aberration « brune » (toutes les parties noires étaient devenues brunes), un adulte au plumage d’été typique et avec pattes et pieds dépigmentés (rosés) et un oisillon avec plumage typique, mais doté de plumes blanchâtres sur le dos et la couverture alaire. L’albinisme et les mutations « brunes » sont des caractères héréditaires, tandis que les deux autres aberrations de couleur ont probablement été acquises et peuvent être le résultat de maladie, de malnutrition ou d’autres facteurs inconnus.